The Influence of Product Trends, Store Atmosphere, and Service Quality on Purchasing Decisions at R2 Collection Rantauprapat - Azizah Anzani Tanjung; Zufrie (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the influence of product trends, store atmosphere, and service quality on consumer purchasing decisions at R2 Collection Rantauprapat. This study used a quantitative method with an associative approach. The population in this study was all consumers who had made purchases at R2 Collection Rantauprapat. The sampling technique used accidental sampling with a total of 100 respondents. Data collection was conducted through questionnaires using a Likert scale. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial t-tests, simultaneous F-tests, and the coefficient of determination (R²). The results showed that product trends and service quality had a positive and significant influence on consumer purchasing decisions.Meanwhile, store atmosphere did not have a significant influence on consumer purchasing decisions. Simultaneously, product trends, store atmosphere, and service quality had a positive and significant influence on consumer purchasing decisions at R2 Collection Rantauprapat. The coefficient of determination (R²) value of 0.735 indicates that 73.5% of the variation in purchasing decisions can be explained by the three independent variables in this study, while the remaining 26.5% is influenced by factors outside the research model.